2017 IEEE 11th International Conference on Self-Adaptive and Self-Organizing Systems (SASO) 2017
DOI: 10.1109/saso.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Self-Stabilising Target Counting in Wireless Sensor Networks Using Euler Integration

Abstract: Abstract-Target counting is an established challenge for sensor networks: given a set of sensors that can count (but not identify) targets, how many targets are there? The problem is complicated because of the need to disambiguate duplicate observations of the same target by different sensors. A number of approaches have been proposed in the literature, and in this paper we take an existing technique based on Euler integration and develop a fully-distributed, self-stabilising solution. We derive our algorithm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…That is, we take the sensors to be arranged in two rows of three sensors each, and each sensor is overlapping with its neighbours, and no other sensor. This type of topology is similar to some examples analysed by Pianini et al [5].…”
Section: (C) Random and Grid Topologiessupporting
confidence: 89%
See 2 more Smart Citations
“…That is, we take the sensors to be arranged in two rows of three sensors each, and each sensor is overlapping with its neighbours, and no other sensor. This type of topology is similar to some examples analysed by Pianini et al [5].…”
Section: (C) Random and Grid Topologiessupporting
confidence: 89%
“…By applying the algorithm of Baryshnikov and Ghrist [4] to the same topology, the estimated target count is zero, which does not correspond to any feasible distribution. Experimental results in a study by Pianini et al [5] have also confirmed the difficulty in obtaining reliable results with this algorithm.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The key problems with multi-camera configurations are co-ordination and control of individual, heterogeneous cameras such that they perform collaboratively [56]. The set of cameras should in other words behave as a CAS in order to react to local and global contingencies, and to provide distributed global functions [57].…”
Section: Public Safety and Securitymentioning
confidence: 99%
“…The techniques can also provide a substrate for exploring location-or topology-dependent processes that are specified as global functions and then decomposed onto the spatial structure (cf. [43]).…”
Section: ) Resilience Strategymentioning
confidence: 99%